Transitional Learning in a Transitional Labor Market - Ellen Scully-Russ (Adult Education Research Conference, 2014)
Precarious work traps workers in a cycle of marginalization. Though there is research on how individuals can break this cycle, little is known about how learning can change the conditions of marginalization. This study explores the learning processes that can also improve the conditions of precarious work.